Transition Strategies of Green MSMEs: A Sequential Explanatory Design Mix Method Analysis - Rizaldi Yusfiarto (East Java Economic Journal, 2023)
The purpose of this research is to predict the main target and identify relevant antecedent constructs on the transition in MSMEs green business practices. The sample is MSMEs Managers/Owners in the Java region, as many as 287 respondents were analyzed using Mixed Methods (Sequential Explanatory Design). The findings show that government rules and regulations positively encourage the value of environmental practices and the intention of MSMEs to switch to green practices. Furthermore, government support, partnerships and co-creation are effective ways of promoting the shift in MSME green business practices. However, the high cost of transitioning to green practices remains a major barrier for MSMEs, while it needs to be a multi-sectoral focus